Cell-based therapy in the management of Class III Miller's recession - A case report with 45-month follow-up - R P Meenakshi; R Kiruba; K V Arun; G Sivaram; Deepavalli Arumuganainar; K Kaveri (Wolters Kluwer Medknow Publications, 2023)
Miller's Class III gingival recessions (GRs) have always posed a challenge to the clinicians in terms of achieving complete root coverage (CRC). In the present case, a cell-based therapy with autologous fibroblasts seeded onto a Type 1 collagen membrane, through an in-vitro culturing method was utilized. The fibroblasts-seeded membrane was surgically placed under a laterally repositioned flap. The patient presented with a CRC, which was stable even at the postoperative period of 45 months. In addition, a 3-mm substantial gain in the width of keratinized tissue was achieved and maintained throughout the postoperative period. Hence, the results of the cell-seeded therapy emphasize that it can serve as an effective alternative method for the management of Miller's Class III GRs.